Analisis Kelayakan Bisnis Pada Usaha Keripik Pisang Coklat Lumer - Nuradilah, Ayu; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Chocolate banana chips are a snack made from fried banana slices and flavored with chocolate. The aim of this research is to determine the total costs, total income, gross profit, BEP value and R/C value at the chocolate banana chips factory located in Karawang Regency. This research method is quantitative descriptive analysis. Locations were determined by purposive sampling. 100 respondents were taken using numerical methods. Primary and secondary data are used as data. This research resulted in total costs of IDR 4,444,10,151,719 per month, total income of IDR 14,422,500 per month, and total income of IDR 62,892 per month. The unit break-even point (BEP) is 810 packs/month and the weight of each pack is 250 grams. This value is lower than the break-even point (BEP) based on average production of 1163/month and price of 8650/pack. This value is lower than the product price of IDR 12,417. Chocolate Banana Chips have an R/C value of 1.43. Based on the R/C value, it is estimated that the R/C value is high and feasible for chocolate banana processing companies.